Latent Destinies : Cultural Paranoia and Contemporary U.S. Narrative - O'Donnell, Patrick, 1948- (Book collections on Project MUSE., 2000)
Uses a discussion of contemporary films and literary works to present an understanding of paranoia as a defining element in postmodern late-capitalist structure.